Impulse initiation in engrafted pluripotent stem cell-derived cardiomyocytes can stimulate the recipient heart: report - Stüdemann, Tim; Schwarzová, Barbora; Schneidewind, Till; Geertz, Birgit; von Bibra, Constantin; Nehring, Marie; Rössinger, Judith; Wiegert, Simon; Eschenhagen, Thomas; Weinberger, Florian (Stem cell reports, 2024)
Transplantation of pluripotent stem cell-derived cardiomyocytes is a novel promising cell-based therapeutic approach for patients with heart failure. However, engraftment arrhythmias are a predictable life-threatening complication and represent a major hurdle for clinical translation. Thus, we wanted to experimentally study whether impulse generation by transplanted cardiomyocytes can propagate to the host myocardium and overdrive the recipient rhythm. We transplanted human induced pluripotent stem cell-derived cardiomyocytes expressing the optogenetic actuator Bidirectional Pair of Opsins for Light-induced Excitation and Silencing (BiPOLES) in a guinea pig injury model. Eight weeks after transplantation ex vivo, Langendorff perfusion was used to assess electrical coupling. Pulsed photostimulation was applied to specifically activate the engrafted cardiomyocytes. Photostimulation resulted in ectopic pacemaking that propagated to the host myocardium, caused non-sustained arrhythmia, and stimulated the recipient heart with higher pacing frequency (4/9 hearts). Our study demonstrates that transplanted cardiomyocytes can (1) electrically couple to the host myocardium and (2) stimulate the recipient heart. Thus, our results provide experimental evidence for an important aspect of engraftment-induced arrhythmia induction and thereby support the current hypothesis that cardiomyocyte automaticity can serve as a trigger for ventricular arrhythmias.